1999
DOI: 10.1590/s0041-87811999000600008
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between obsessive-compulsive disorders and diseases affecting primarily the basal ganglia

Abstract: Obsessive-compulsive disorder (OCD) has been reported in association with some neurological diseases that affect the basal ganglia such as Tourette's syndrome, Sydenham's chorea, Parkinson's disease, and Huntington's disease. Furthermore, studies such as neuroimaging, suggest a role of the basal ganglia in the pathophysiology of OCD. The aim of this paper is to describe the association of OCD and several neurologic disorders affecting the basal ganglia, report the existing evidences of the role of the basal ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Secondly, OCD is frequently seen in patients with basal ganglia dysfunctions such as Tourette’s syndrome, Sydenham’s chorea and Huntington’s disease. Obsessive-compulsive symptoms in several neurological disorders affecting the basal ganglia confirm its role in the pathophysiology of OCD [ 79 , 80 ]. Basal ganglia is an area where the serotonin and dopamine systems interact extensively and these two systems are important in the pathophysiology of the disease [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, OCD is frequently seen in patients with basal ganglia dysfunctions such as Tourette’s syndrome, Sydenham’s chorea and Huntington’s disease. Obsessive-compulsive symptoms in several neurological disorders affecting the basal ganglia confirm its role in the pathophysiology of OCD [ 79 , 80 ]. Basal ganglia is an area where the serotonin and dopamine systems interact extensively and these two systems are important in the pathophysiology of the disease [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between disorders of the basal ganglia and symptoms of Obsessive Compulsive Disorder (OCD) has been previously established (1–5,7,16–21). Patzold and Brune (3) reported a case of a 42‐year‐old woman with HD who experienced obsessions successfully treated with sertraline.…”
Section: Discussionmentioning
confidence: 99%
“…, 2010). The role of dopamine is not as clear, as cases of OCD have been reported in both hypodopaminergic and hyperdopaminergic pathologies [Parkinson’s and Huntington’s diseases (Cummings & Cunningham, 1992; Maia et al. , 1999; Alegret et al.…”
Section: Perspectivesmentioning
confidence: 99%
“…Alongside the development of imaging and animal models, a number of case reports have suggested that basal ganglia do indeed play a major role in OCD development. The first articles reported the late appearance of OCD in patients with known basal ganglia degenerative diseases, among which were Parkinson's and Huntington's diseases (Cummings & Cunningham, 1992;Maia et al, 1999;Alegret et al, 2001;Harbishettar et al, 2005). Most articles, however, have reported cases of OCD that began after focal lesions of basal ganglia.…”
Section: Fortuitous Clinical Observationsmentioning
confidence: 99%
See 1 more Smart Citation